2024
DOI: 10.2196/51523
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Large Language Models for the National Premedical Exam in India: Comparative Analysis of GPT-3.5, GPT-4, and Bard

Faiza Farhat,
Beenish Moalla Chaudhry,
Mohammad Nadeem
et al.

Abstract: Background Large language models (LLMs) have revolutionized natural language processing with their ability to generate human-like text through extensive training on large data sets. These models, including Generative Pre-trained Transformers (GPT)-3.5 (OpenAI), GPT-4 (OpenAI), and Bard (Google LLC), find applications beyond natural language processing, attracting interest from academia and industry. Students are actively leveraging LLMs to enhance learning experiences and prepare for high-stakes ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…This may be because the Internal Medicine of TCM questions were mostly presented in case formats, where LLMs showed greater pro ciency in extracting and processing internal information. Subject-level accuracy illustrates the suitability of various models for distinct domains, providing invaluable guidance for users seeking to choose a model tailored to their speci c requirements 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be because the Internal Medicine of TCM questions were mostly presented in case formats, where LLMs showed greater pro ciency in extracting and processing internal information. Subject-level accuracy illustrates the suitability of various models for distinct domains, providing invaluable guidance for users seeking to choose a model tailored to their speci c requirements 24 .…”
Section: Discussionmentioning
confidence: 99%
“…ChatGPT, developed by OpenAI, has undergone multiple version updates since its release. The latest iteration, GPT-4, was launched on March 14, 2023, integrating enhanced language generation capabilities with improved multi-round dialogue processing 24 .…”
Section: Gpt-4mentioning
confidence: 99%
“…The importance and implications of AI tools are swiftly increasing in various sections of society ( 34 ). In this context, this study’s findings are vital for understanding the ChatGPT knowledge for its implementation in educational settings ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Farhat et al (34) provided valuable insights into the performance of ChatGPT-3.5, ChatGPT-4, and Bard in answering the questions. The authors reported that CHAT GPT-4 is the perfect model, highlighting its potential role in education.…”
Section: Discussionmentioning
confidence: 99%
“…Large language models (LLMs), such as ChatGPT-4, Gemini, and Microsoft Copilot, have revolutionized the field of artificial intelligence (AI) by demonstrating an unprecedented ability to understand and generate human-like text [1][2][3]. These chatbot models are trained on diverse internet datasets, allowing them to acquire vast amounts of knowledge and language nuances [4,5]. LLMs perform a variety of tasks, from answering queries to generating coherent and contextually appropriate responses, making them potent tools for information dissemination and decision support across multiple domains [6,7].…”
Section: Introductionmentioning
confidence: 99%